2012
DOI: 10.1016/j.otpol.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Pooperacyjne zawroty głowy związane z nadmierną długością protezki strzemiączka – diagnostyka radiologiczna

Abstract: The aim of the study was to describe the value of High Resolution Computed Tomography (HRCT) with MPR and VR reconstruction of the temporal bone in patients with persistent vertigo after stapedotomy. High Resolution Computed Tomography with MPR and VR reconstruction of the temporal bone in the axial and coronal planes with 0.625 - mm slice thickness were performed in 2 patients with persistent vertigo after stapedotomy. Persistent vertigo were observed in 2 patients suffered from otosclerosis several months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…This is performed through the ear canal and the stapes is replaced with a prosthetic stapes piston. The length of the prosthetic must be fit properly for each individual, as a long prosthesis can lead to severe vertigo (53) and a short prosthesis may not adequately conduct sound or can become displaced (54,55). The vast majority of patients fit the same length prosthesis (e.g., either 4.25 mm if a conventional prosthesis is selected or 4.5 mm if a shape memory alloy prosthesis is used) (56).…”
Section: Discussionmentioning
confidence: 99%
“…This is performed through the ear canal and the stapes is replaced with a prosthetic stapes piston. The length of the prosthetic must be fit properly for each individual, as a long prosthesis can lead to severe vertigo (53) and a short prosthesis may not adequately conduct sound or can become displaced (54,55). The vast majority of patients fit the same length prosthesis (e.g., either 4.25 mm if a conventional prosthesis is selected or 4.5 mm if a shape memory alloy prosthesis is used) (56).…”
Section: Discussionmentioning
confidence: 99%
“…The prosthesis length which is calculated upon FID has a key role on the success of stapedotomy procedure. A long prosthesis may cause vertigo and a short prosthesis may not be able to reconstruct the hearing or may be prone to dislocation ( Scierski et al., 2012 , Portmann et al., 2007 ). According to Lippy WH et al., there is no need for measuring for determination of PL except for the ones with congenital deformities ( Lippy and Berenholz, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a short prosthesis may not be able to conduct the sound or it may be very susceptible to dislocation. Measurement of the distance between long process of incus and stapedial foot plate is advocated by many surgeons, on the other hand, there are some who do not perform this measurement and use a fixed length of prosthesis ( Scierski et al., 2012 , Portmann et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the gender issue was noticed (in the author's own study, an increased level of anxiety was observed more often in younger women [9]). People experiencing highly annoying tinnitus more often experience more negative emotions, such as dissatisfaction with life, difficulties in achieving relaxation, anxiety, tension or stress [23] (it may even increase the volume and nuisance of tinnitus). Cognitive impairment is also emphasized in these people.…”
Section: Functioning Of Patients With Aileries Accompanying Otosclerosismentioning
confidence: 99%
“…Constantly feeling it interferes with everyday functioning and reduces the quality of life to a greater or lesser extent. In a postoperative study conducted by a group of doctors [23], two patients who experienced dizziness a few months after the operation reported, after the stapes prosthesis was shortened, the dizziness disappeared. The risk of tinnitus in a group of patients who did not experience it before the surgery, however, in the vast majority of patients it disappears after a few days or weeks.…”
Section: Postoperative Complications -Patient Functioningmentioning
confidence: 99%